Breaking social media fads and uncovering the safety and efficacy of mouth taping in patients with mouth breathing, sleep disordered breathing, or obstructive sleep apnea: A systematic review - Jess Rhee; Alla Iansavitchene; Sonya Mannala; M. Elise Graham; Brian Rotenberg (PLoS ONE, 2025)
Background Social media has contributed to a potentially unsafe trend of nighttime mouth taping for individuals with mouth breathing, sleep disordered breathing, or sleep apnea as a home remedy to treat these issues. This systematic review is aimed to highlight any potential benefits or harms with this practice. Methods A comprehensive librarian-designed literature search was performed using PRISMA guidelines. Using search terms, “mouth taping, adhesive mouthpiece, porous oral patch, surgical tape, breathing mouthpiece, sleep, microsleep, breath, breathing, or mouth breathing”, MEDLINE, Embase, and Google Scholar were searched from February 1999 to February 2024. Covidence software was used for screening and data entry performed into a data collection sheet designed a priori. Results Covidence software was utilized to screen 120 articles. After 34 duplicates were removed, 86 articles were screened by two independent reviewers. Sixty-two were excluded. Twenty-four went on to full text review and 10 met inclusion criteria with a total of 213 patients. Two studies showed statistically significant improvement in established markers of sleep apnea such as apnea-hypopnea index (AHI) or oxygen desaturations. Other studies showed that mouth taping offered no differences and even discussed potential risks including asphyxiation in the presence of nasal obstruction. Many studies excluded anyone with nasal obstruction or pathology. Conclusion The social media trend of mouth taping for individuals with mouth breathing, sleep disordered breathing, or sleep apnea has been reviewed. Based on the data presented by these 10 different studies, it seems that there is a potentially serious risk of harm for individuals indiscriminately practicing this trend. Further studies are required to elucidate any clinical benefit this practice may have.